Review of Direct Yaw Moment Control System for Automobile - LIAN Yufeng; HUANG Jianan; FENG Wenhuan; LIU Shuaishi; DONG Bing (Kongzhi Yu Xinxi Jishu)
Direct yaw moment control (DYC) system is used to effectively prevent the vehicle from moving sideways in the event of unexpected dangers in order to ensure stability and safety of automobile driving. The currently DYC systems are mostly in a hierarchical structure. This paper starts with an analysis on the DYC system's architecture from three perspectives: automobile state estimation and environmental perception, direct yaw moment controller design and moment distribution method. The focus then shifts to the acquisition and processing methods of state information, such as automobile speed, vehicle-to-vehicle spacing, road surface information, yaw rate, vehicle centroid sideslip angle. It also presents a reference model for vehicle dynamics, control structure and design methods for controlling different variables as the upper-level controllers; the distribution method of vehicle yaw moment in the lower-level controller are then presented. It is concluded with summary on some existing issues in the DYC systems and their future development trends.